Interplanetary external driven quasidynamo as the origin of geomagnetic jerks correlated with length of day and gravity anomaly: The origin of 5.9-years and 11-years and semi-annual periodic geophysical signals and Jovian planets alignments as the origin of the abrupt geomagnetic jerks - LUTEPHY, Mohsen (Contributions to Geophysics and Geodesy, 2018)
We report phenomenological inevitable correlation between the Sun’s magnetic field oscillation through the Earth and the Jupiter, with sinusoidal geomagnetic jerks observed at the Earth, additionally aligned with the gravity and length of day sinusoidal variations and we observe too that the Sun and Jovian planets alignments with Jupiter are origin of the observable abrupt geomagnetic jerks whether historical or new, and experimental results demonstrate a possible explanation on the base of the planetary induced currents upon the metallic liquid cores of the planets upon the varying external magnetic fields as the source of heat flows continued by frictional turbulent and convectional fluid fluxes, amplified and expanding by the Earth magnetic field and observations are showing too that it should be an electric coupling effect between metallic cores of the planets, under the magnetic field oscillation so that Jupiter conductive metallic region interacts with Earth metallic core while the Sun’s magnetic field is oscillating through the Jupiter and we see a relation between secular variation of the Earth’s magnetic field and long term trend of 5.9-years signals as a new method to measure geomagnetic secular variation by LOD signals.